PEWARISAN POLA PEWARISAN PEDALANGAN GAYA I NYOMAN RAJEG: PEDALANGAN - janamajaya jana; Dru Hendro; I Dewa Ketut Wicaksandita (JURNAL DAMAR PEDALANGAN, 2026)
This study examines the inheritance pattern of the I Nyoman Rajeg puppetry style in Tunjuk Village, Tabanan, as a dynamic and reflective system of cultural transmission. The research aims to describe the manifestation of transmission pathways within the puppeteer family, analyze the comparative characteristics of intergenerational regeneration methods, and explain their implications for the formation of individual artistic styles. A qualitative approach with a case study design was employed, involving three generations of puppeteers as primary subjects. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using the Miles and Huberman interactive model, supported by theories of cultural transmission, sanggit–garap, and restored behavior. The findings reveal that inheritance operates through the simultaneous interaction of vertical, horizontal, and oblique transmission pathways, shaping distinct learning processes across generations. The third generation emphasizes experiential learning, the fourth relies on literary reconstruction and self-reflection, while the fifth integrates familial tradition, social environment, and formal education. These variations produce differentiated artistic styles that are not merely replicative but innovatively grounded within traditional frameworks. This study formulates the concept of “Reflective Performative Inheritance,” highlighting that the sustainability of tradition lies not in formal uniformity but in creative reinterpretation across generations. The findings affirm that Balinese puppetry is a living tradition that continuously evolves through the dialectic interplay of heritage, experience, and artistic consciousness.